The role of cGMP as a mediator of lipolysis in bovine oocytes and its effects on embryo development and cryopreservation - Schwarz, Kátia R. L.; de Castro, Fernanda C; Schefer, Letícia; Botigelli, Ramon C. [UNESP]; Paschoal, Daniela M.; Fernandes, Hugo; Leal, Cláudia L. V. (Public Library of Science (PLoS), 2018)
This study aimed to determine the influence of cyclic guanosine 3’5’-monophosphate (cGMP) and cGMP-dependent kinase (PKG) during in vitro maturation (IVM) on lipolysis-related parameters in bovine cumulus-oocyte complexes (COCs), and on embryo development and cryosurvival. COCs were matured with cGMP/PKG modulators and assessed for metaphase II rates (MII), cGMP levels, lipid content in oocytes (OO), transcript abundance for genes involved in lipolysis (ATGL) and lipid droplets (PLIN2) in cumulus cells (CC) and OO, and presence of phosphorylated (active) hormone sensitive lipase (HSLser563) in OO. Embryo development, lipid contents and survival to vitrification were also assessed. Phosphodiesterase 5 inhibition (PDE5; cGMP-hydrolyzing enzyme) with 10-5M sildenafil (SDF) during 24 h IVM increased cGMP in COCs (56.9 vs 9.5 fMol/COC in untreated controls, p<0.05) and did not affect on maturation rate (84.3±6.4% MII). Fetal calf serum (FCS) in IVM medium decreased cGMP in COCs compared to bovine serum albumin (BSA) + SDF (19.6 vs 66.5 fMol/COC, respectively, p<0.05). FCS increased lipid content in OO (40.1 FI, p<0.05) compared to BSA (34.6 FI), while SDF decreased (29.8 and 29.6 FI, with BSA or FCS, respectively p<0.05). PKG inhibitor (KT5823) reversed this effect (38.9 FI, p<0.05). ATGL and PLIN2 transcripts were detected in CC and OO, but were affected by cGMP and PKG only in CC. HSLser563 was detected in OO matured with or without modulators. Reduced lipid content in embryos were observed only when SDF was added during IVM and IVC (27.6 FI) compared to its use in either or none of the culture periods (34.2 FI, p<0.05). Survival to vitrification was unaffected by SDF. In conclusion, cGMP and PKG are involved in lipolysis in OO and possibly in CC and embryos; serum negatively affects this pathway, contributing to lipid accumulation, and cGMP modulation may reduce lipid contents in oocytes and embryos, but without improving embryo cryotolerance.